1999
DOI: 10.1038/5593
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor gene therapy of liver cirrhosis in rats

Abstract: Liver cirrhosis is the irreversible end result of fibrous scarring and hepatocellular regeneration, characterized by diffuse disorganization of the normal hepatic structure of regenerative nodules and fibrotic tissue. It is associated with prominent morbidity and mortality, and is induced by many factors, including chronic hepatitis virus infections, alcohol drinking and drug abuse. Hepatocyte growth factor (HGF), originally identified and cloned as a potent mitogen for hepatocytes, shows mitogenic, motogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
416
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 552 publications
(447 citation statements)
references
References 31 publications
24
416
0
4
Order By: Relevance
“…On the other hand, Mizuno et al 3 reported that HGF supplement induced an increase in the endogenous HGF level in kidney in mice, but the increase was less than two-fold versus the saline control. Ueki et al 42 reported an increase in endogenous HGF level in circulating plasma after transduction with the HGF gene, but the increase was at most four-fold versus the control. (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mizuno et al 3 reported that HGF supplement induced an increase in the endogenous HGF level in kidney in mice, but the increase was less than two-fold versus the saline control. Ueki et al 42 reported an increase in endogenous HGF level in circulating plasma after transduction with the HGF gene, but the increase was at most four-fold versus the control. (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Probably kidney, like muscle, 24 is a source of hHGF, in that cells, when efficiently transfected with the plasmid, are converted into hHGF protein producers. We 25 and other authors 28 showed previously that exogenous hHGF induces endogenous production of rHGF. In the present study, both hHGF-treated groups not only showed high levels of plasma hHGF but increased endogenous rHGF levels, corroborating that gene hHGF electrotransfer clearly increases rat renal HGF production.…”
Section: Discussionmentioning
confidence: 67%
“…Among the many approaches for gene transfer in vivo using viral or nonviral vectors, the HVJ-liposome method is thought to be the most suitable for antiangiogenic gene therapy because HVJ-liposomes can maintain gene expression for long periods by repeated injection, without apparent toxicity, inflammation or significant immunogenicity in vivo. [31][32][33][34] Although the transfection efficiency of HVJ-liposomes is relatively lower than that of viral vectors such as adenoviral vectors, repeated transductions with HVJliposomes make it feasible to express continuously an indicated gene, and thus may be more advantageous for antiangiogenic therapy against cancer. Boehm et al 35 reported that cyclical therapy with the antiangiogenic proteins, angiostatin and endostatin, resulted in permanent tumor arrest at a microscope dormant size with blocked angiogenesis, even after the therapy was discontinued.…”
Section: Resultsmentioning
confidence: 99%